Foot plantar pressure monitoring system using EMED®-A: preliminary results - Mohamad Ghazali, Aina Mardhiyah; Wan Hasan, Wan Zuha; Ahmad, S. A.; Hamidon, Mohd Nizar; Harun @ Ramli, Hafiz Rashidi (IEEE, 2017)
The aim of this study was to assess the repeatability of the EMED®-A and identify the repeatability of data for different types of measurements (walking without load, walking with load, standing without load, and standing with load). Each load weighing 1.5 kg must be hold at left and right hands. Contact area (CA), maximum force (F), peak pressure (PP) were calculated. In addition, coefficient of variation (CV) is calculated for repeatability of EMED®-A. In conclusion, the EMED®-A foot plantar pressure monitoring system was found to be repeatable and can be used as valuable tool for plantar pressure distribution assessment.